Sweet potato development - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1992)
Sweet potato breeders at the Asian Vegetable Research And Development Center (AVRDC) have developed several true seed populations of sweet potato. This has been achieved through polycrosses of clones from many geographical zones. The polycross...